A natural combinatorial chemistry strategy in acylpolyamine toxins from Nephilinae orb-web spiders - Palma, Mario Sergio [UNESP]; Nakajima, T. (Taylor & Francis Inc, 2005)
The present study shows how nature combined a small number of chemical building blocks to synthesize the acylpolyamine toxins in the venoms of Nephilinae orb-web spiders. Considering these structures in four parts, it was possible to rationalize a way to represent the natural combinatorial chemistry involved in the synthesis of these toxins: an aromatic moiety is connected through a linker amino acid to a polyamine chain, which in turn may be connected to an optional tail. The polyamine chains were classified into seven subtypes (from A to G) depending on the way the small chemical blocks are combined. These polyamine chains may be connected to one of the three possible chromophore moieties: 2,4-dihydroxyphenyl acetic acid, or 4-hydroxyindole acetic acid, or even with the indole acetic group. The connectivity between the aryl moiety and the polyamine chain is usually made through an asparagine residue; optionally a tail may be attached to the polyamine chain; nine different types of tails were identified among the 72 known acylpolyamine toxin structures. The combinations of three chromophores, two types of amino acid linkers, seven sub-types of polyamine backbone, and nine options of tails results in 378 different structural possibilities. However, we detected only 91 different toxin structures, which may represent the most successful structural trials in terms of efficiency of prey paralysis/death.
Keywords: acylpolyamine toxins; orb-web spiders; spider toxins; combinatorial chemistry